2023
DOI: 10.1088/1361-648x/acbb4a
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced spin-polarized transport and controllable valley-triplet pairing states in a silicene-superconductor junction

Abstract: We theoretically investigate the spin-polarized subgap transport and valley-triplet pairing states in a silicene-superconductor junction. By using the nonequilibrium Green's function, it is found that the subgap conductance is strongly affected by the spin polarization induced by an off-resonant circularly polarized light. More importantly, the presence of valley-mixing scattering at the interface could result in a valley-triplet Andreev reflection (AR) process, where the incident electrons and reflected holes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…This phenomenon has also been observed in F/S junctions [14,24] and F/S/ferromagnet double-barrier junctions [17] recently. In particular, Huang [57] reported that conductance peak splitting occurs in a silicene-superconductor junction. In contrast to previous work, Huang focused on the valley degree of freedom rather than the spin degree of freedom and discovered that the conductance peak splitting results from competition between the valley-singlet and valley-triplet states induced in normal silicene.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon has also been observed in F/S junctions [14,24] and F/S/ferromagnet double-barrier junctions [17] recently. In particular, Huang [57] reported that conductance peak splitting occurs in a silicene-superconductor junction. In contrast to previous work, Huang focused on the valley degree of freedom rather than the spin degree of freedom and discovered that the conductance peak splitting results from competition between the valley-singlet and valley-triplet states induced in normal silicene.…”
Section: Resultsmentioning
confidence: 99%
“…N Kσ > N K ′ σ , leading to the AF-induced valley polarization in silicene. This differs from the ferromagnetic exchange field or off-resonant light, which generates spin polarization in silicene [39,40]. When an electric field is also applied in the AF region, the spin degeneracy for the K and/or K ′ valleys is lifted, giving rise to the spin polarization in silicene.…”
Section: Band Structures and The Af-induced Valley Polarizationmentioning
confidence: 95%
“…In this paper, we propose a silicene-based AF/homo-or bulk-SC junction to study the valley-polarized subgap transport. The antiferromagnetic exchange field λ AF itself can induce valley polarization in silicene without the aid of an electric field, unlike the ferromagnetic exchange field or light field only generating spin polarization [39,40]. It is shown that, for a large λ AF , the Andreev-resonant peak at gap edge is supplanted by broadened features for the homo-SC model whereas by a sharp conductance dip for the bulk-SC model.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations